MODEL PANTUN DITINJAU DARI KESEPADANAN STRUKTUR KALIMAT DASARNYA - Hidayatul Astar (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
As a specific communication realization in society, pantun can be researched in various aspects of language. The aspect studied in this paper is the structural model whice is viewed from the structural similarity basic sentence. The purpose of this reserch is to reveal the numbers of pantun models based on the similarity of elements, the composition of elements, syntactic functions, and the types of sentences between odd and even lines. The method used is descriptive qualitative. The analysis carried out follows Alwi et al., especially relating elements, syntactic functions, and sentence types. After analyzing 50 pantun, it revealed that three pantun models. The similarity level of the three pantun models are 100%, 62.50-87.50%, and 12.50-050% respectively. Each line can have at least one and a maximum four elements. The syntactic function is explicitly dominant is predicative as the subjects often deleted. The elements can be composed in ordinary, inversion, or combination of both an ordinary and iversion ways. Meanwhile, the types of sentences that make up the pantun are single sentences and compound sentences.